Sosialisasi dan Edukasi Budidaya dan Prospek Ekonomi Buah Alpukat (Persea americana) di Desa Wih Terjun Pegasing Aceh Tengah - Ratnawati, Ratnawati; Kamarudin, Anna Permatasari; Yusnadi, Alja; Basyirah, Basyirah; Ramiati, Ramiati; Suratman, Bambang; Amna, Amna; Amiruddin, Amiruddin; Zainuddin, Zainuddin; Subayu, Arya; Frasiska, Widiya; Rejeki, Desi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Wih Terjun is one of the villages located in Pegasing Subdistrict, Central Aceh. Its environmental conditions, situated in mountainous and hilly areas, are highly suitable for cultivating avocado plants. The purpose of this Community Service (PkM) activity was to provide socialization and education to the community of Wih Terjun Village regarding the cultivation and economic prospects of avocado fruit (Persea americana).The partners participating in the program consisted of 22 individuals, including housewives and teenage girls. The tools and materials used were glass cups, plastic cups, toothpicks, tissue paper, and a water spray bottle. The materials included water and avocado seeds. The results of the PkM implementation showed an increase in participants’ knowledge about avocado plants, including their benefits and properties. The advantages of avocados is their high nutritional content, which can help prevent stunting. In conclusion, through this PkM activity, the community is now able to plant and cultivate avocado plants using either the water method or soil media. This method is simple and can be practiced by anyone.